Neuroimmunological Registries in Germany - Thiel, S.; Leypoldt, F.; Röpke, L.; Wandinger, K. P.; Kümpfel, T.; Aktas, O.; von Bismarck, O.; Salmen, A.; Ambrosius, B.; Ellrichmann, G.; Antony, G.; Dankowski, T.; Ziegler, A.; Stahmann, A.; Meyer, C.; Eichstädt, K.; Buckow, K.; Meißner, T.; Thibaut, J.; Khil, L.; Berger, K.; Gold, R.; Hellwig, K. (Neurology International Open, 2018)
Several neuroimmunological registries have been established in Germany during the last 10 years. The common aim is to investigate the course of different diseases, mainly under various therapeutic conditions, to identify predictive factors as well as the side effects of immunomodulating therapies. Six nationwide neuroimmunological registries will be presented in this article. The German Network for Research on Autoimmune Encephalitis (GENERATE) with more than 40 participating clinical centers and 570 documented patients (September 2016) collects data and biomaterials of autoimmune encephalitis with known and unknown antibodies. The registry coordinates and mediates between scientists and clinicians and acts as a platform for the development of guidelines and procedures. The neuromyelitis optica study group (NEMOS) has established a national registry for patients with neuromyelitis optica and neuromyelitis optica spectrum disorders. In addition to 22 academic hospitals, 17 regional hospitals and several practices are participating. Currently, 250 patients are enrolled. Moreover, NEMOS is now establishing a prospective patient cohort (NationNMO) within the competence network multiple sclerosis. Current research focuses on treatment strategies for relapses and interval therapy of neuromyelitis optica. The competence network multiple sclerosis has initiated a multi-center, prospective cohort study of patients with clinically isolated syndrome (CIS) or relapsing-remitting multiple sclerosis (MS) (NationMS), with the aim of long-term follow-up and clinical and paraclinical characterization of the patients. Between August 2010 and December 2014, 1,212 patients in 22 university und non-university centers were enrolled in the NationMS cohort. Standardized clinical data as well as biomaterial and MRI images were collected and stored. The German MS Society (DMSG, Bundesverband e.V.) established in 2001 a long-term project to obtain a consistent and reliable overview of MS patients in Germany. Since 2014 the registry has been revised comprehensively, with the main purpose of establishing a permanent data repository for healthcare research while ensuring the collection, storage and provision of data over decades and enabling the description of long-term outcomes. Currently, more than 170 German centers are participating and over 48,000 patients are enrolled in the registry. Since 2013, the competence network multiple sclerosis has established the immunotherapy registry REGIMS with the objective to obtain information on incidence, type and characteristics of adverse events of new immunomodulating therapies for patients with multiple sclerosis or clinical isolated syndrome. As of January 2017 more than 700 patients have been recruited from 36 active centers. The German Multiple Sclerosis and Pregnancy Registry aims to obtain safety information of disease modifying drug exposure during pregnancy. In addition to safety aspects, disease course during pregnancy and postpartum and the identification of predictors of disease activity are investigated. During the last ten years 1,500 pregnant MS patients were prospectively enrolled in the registry and at least 250 new pregnancies are followed every year. These six registries make an important epidemiological and scientific contribution. Numerous colleagues from clinics and practice support these registries. The objective is the closer understanding of the disease course, the influence of therapeutic decisions and thus the improvement of counseling and care.
Keywords: neuroimmunological registries; autoimmune encephalitis; neuromyelitis optica spectrum disorders; multiple sclerosis